CHARACTERISTICS OF PHYTOTHERAPEUTIC USE DURING PREGNANCY AND IN THE POSTNATAL PERIOD: INDICATIONS, LIMITATIONS, AND RISKS (LITERATURE REVIEW AND ORIGINAL RESEARCH) - О. Волошин; Л. Волошина; О. Доголіч; Г. Бачук- Понич; І. Окіпняк (Bukovynian State Medical University, 2023)
Increase in the morbidity of women during pregnancy and in the postnatal period, the known limitations using of modern synthetic drugs cause the search for ways of medical assistance, in particular use of phytotherapy. Aim: highlight the world and own experience of using phytotherapeutic agents during pregnancy and in the postnatal period, indications, limitations and threats. Materials and methods: used available monographic and journal sources in the electronic systems MED Line, EMBASE, Scopus, Web of Science using methods of analysis, comparison and generalization. Results. It has been established that scientists from the world's leading scientifi c centers state a growing interest in using of phytotherapy methods as one of the important approaches of medical pluralism in the pathology of pregnancy and in the postnatal period. depending on the level of economic development and the state of the medical industry of the state and the commonality and diff erences of the principles and forms of providing phytotherapeutic assistance. Commonality is that even ancient and simple methods and means of phytotherapy in this contingent of patients, along with modern ones in developed countries, are, albeit to varying degrees, eff ective and safe. In countries with a low socio- ecological level, simple methods according to ancient traditions are still forced to be used, mainly as a self-initiative or on the advice of friends, family, rarely - on the recommendations of specialists without clear recommendations regarding the duration and remote consequences of application, which is unfavorable. There are some diff erence between of using phytotherapy in the developed countries of Europe and USA is that various means, forms of plant factors are mainly manufactured in accordance with modern requirements of the Ministry of Health, are recommended on the basis of evidence- based medicine by properly trained obstetrics and gynecology personnel, modern sources of information are available for the improvement of medical personnel, training of pregnant women. The clear eff ectiveness and side eff ects of herbal preparations, their impact on the body of the mother, fetus and lactation processes are monitored. Various trainings and forms of improving using of herbal medicines are carried out and need for close contacts of obstetriciangynecologists with specialists in complementary and alternative medicine. Conclusions: Modern scientifi c studies testify to the eff ectiveness, safety and necessity of using herbal preparations in the pathology of pregnancy and the postnatal period as one of the important components of medical pluralism. The specifi cs of their use must comply with the requirements of the DMR and be recommended on the basis of evidence- based medicine.